RNA Interference for Functional Genomics and Improvement of Cotton (Gossypium sp.) - Abdurakhmonov, Ibrokhim Y.; Ayubov, Mirzakamol S.; Ubaydullaeva, Khurshida A.; Buriev, Zabardast T.; Shermatov, Shukhrat E.; Ruziboev, Haydarali S.; Shapulatov, Umid M.; Saha, Sukumar; Ulloa, Mauricio; Yu, John Z.; Percy, Richard G.; Devor, Eric J.; et al. (Frontiers in Plant Science, 2016)
RNA interference (RNAi), is a powerful new technology in the discovery of genetic sequence functions, and has become a valuable tool for functional genomics of cotton (Gossypium ssp.). The rapid adoption of RNAi has replaced previous antisense technology. RNAi has aided in the discovery of function and biological roles of many key cotton genes involved in fiber development, fertility and somatic embryogenesis, resistance to important biotic and abiotic stresses, and oil and seed quality improvements as well as the key agronomic traits including yield and maturity. Here, we have comparatively reviewed seminal research efforts in previously used antisense approaches and currently applied breakthrough RNAi studies in cotton, analyzing developed RNAi methodologies, achievements, limitations, and future needs in functional characterizations of cotton genes. We also highlighted needed efforts in the development of RNAi-based cotton cultivars, and their safety and risk assessment, small and large-scale field trials, and commercialisation.